Regional Police Role Of Central Java In Prevention Of Domestic Violence Act In The Family - Wina Angrayini; Sri Endah Wahyuningish (Jurnal Daulat Hukum, 2018)
Domestic violence is still a lot going on regardless of social strata, economic, age, education level even. Polri plays an important role in the prevention of the domestic violence act. The problem is analyzed using the theory and the theory of crime prevention role. The results showed that the Central Java Police's role in the response to domestic violence is at the preventive and repressive efforts. Preventive efforts to optimize the function Binmas in executing is Bhabinkamtibmas by conducting outreach and dissemination to the public. While the repressive efforts carried out through investigation procedure as the provisions of the legislation applicable to the mediation efforts remain to be done. The obstacles that appear in the response to domestic violence in the Central Java Police is the public perception of the cases of domestic violence is considered a regular problem and not a criminal case, the lack of a witness in the trial of domestic violence, limited human resources and infrastructure to protect the victim. As an attempt to overcome these obstacles is to change the public perception that by doing counseling and socialization of domestic violence is routine and ongoing, came to address the witness for questioning as a witness, working with agencies / NGOs and by following the development education specialist of Polwan PPA. Associated with limited facilities and infrastructure in the protection of victims is cooperation with NGOs that provide shelter.Keywords: Prevention; Domestic Violence Act